2022
DOI: 10.3390/ijms23179623
|View full text |Cite
|
Sign up to set email alerts
|

Bis-Cyclic Guanidine Heterocyclic Peptidomimetics as Opioid Ligands with Mixed μ-, κ- and δ-Opioid Receptor Interactions: A Potential Approach to Novel Analgesics

Abstract: The design and development of analgesics with mixed-opioid receptor interactions has been reported to decrease side effects, minimizing respiratory depression and reinforcing properties to generate safer analgesic therapeutics. We synthesized bis-cyclic guanidine heterocyclic peptidomimetics from reduced tripeptides. In vitro screening with radioligand competition binding assays demonstrated variable affinity for the mu-opioid receptor (MOR), delta-opioid receptor (DOR), and kappa-opioid receptor (KOR) across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Studies have shown that mixed opioid agonists can effectively reduce RD and other side effects. [36,37] For example, nalbuphine and dezocine, which are commonly used clinically, are MOR/ KOR partial agonists and both cause weaker RD. [38,39] The diarylmethylpiperazine compound DPI-125, a mixed agonist of the opioid receptor, exhibits strong analgesic properties and a high respiratory safety profile in a rat tail-flick pain model.…”
Section: Mixed Opioid Receptor Agonistsmentioning
confidence: 99%
“…Studies have shown that mixed opioid agonists can effectively reduce RD and other side effects. [36,37] For example, nalbuphine and dezocine, which are commonly used clinically, are MOR/ KOR partial agonists and both cause weaker RD. [38,39] The diarylmethylpiperazine compound DPI-125, a mixed agonist of the opioid receptor, exhibits strong analgesic properties and a high respiratory safety profile in a rat tail-flick pain model.…”
Section: Mixed Opioid Receptor Agonistsmentioning
confidence: 99%